Teratogenic effects of organophosphate insecticides in the etiology of cleft lip palate: literature review (2017)
Objective: Evaluate the scientific evidence about the associated relation between the individuals exposure to organophosphates insecticides with the prevalence of non syndromic cleft lip and palate. Material and Methods: The search of scientific articles was held in the data base of PubMed, Science Direct, Academic Google, Medline, Cochrane and Scielo, published between year 2.000 and 2015, and a series of interviews were held to professionals with a Doctor or Master degree In Toxicology, Public Health, Genetics and Biochemistry that were knowledge about this subject. 25 articles of insecticides were reviewed   and 5 semi structural interviews. Results: A statistical number of studies stablish an association between the exposure to pesticides with teratogenic effects related with the cleft lip and palate; in vivo experimental studies in animals correlate the exposure the organophosphates insecticide Clorpilifos, with the higher prevalence of cleft palate. Conclusion: some studies found associated relation between the exposure to organophosphates insecticides with increased the incidence of birth abnormalities.